Revaluation of a beer industry by-product towards the development of a sustainable product: beer by-product pasta - Souza, Ana; Arias, Ezequiel; Arellano, Veronica; Macarin, Gabriela; Vargha, Sofía; Raggio, Laura Ma. (Frontiers in Food Science and Technology, 2025)
Brewer’s Spent Grain (BSG), a byproduct of the brewing industry, presents environmental and economic challenges due to food waste. Animal feed is its primary use, but its high dietary fiber (DF) and protein content make it suitable for human consumption. BSG contains 30%–70% DF and 19%–36% protein, with essential amino acids, particularly lysine, which is scarce in cereals, making it a valuable ingredient for products like pasta and baked goods. Recent consumer trends favor foods rich in fiber and protein, aligning with increasing awareness of health benefits associated with dietary fiber. Fiber contributes to improved intestinal transit, reduced risk of cardiovascular diseases, and lower incidence of type II diabetes, among other health benefits. Additionally, for every extra 10 g of DF consumed daily, mortality risk decreases by 17%–35%. A study conducted in Uruguay in mid-2023 through an online survey with 851 participants aimed to assess interest in BSG-enriched products. Results showed 86% of respondents were willing to purchase such products, while those opposed expressed concerns about potential unpleasant taste. Participants were categorized into three groups based on their prioritization of nutritional content, fiber, and protein when making purchase decisions. Age was the most significant factor influencing the importance assigned to these nutritional components, with older individuals placing higher importance on fiber and protein content. Overall, the study indicates a favorable public interest in BSG-enriched foods, especially considering their nutritional benefits and affordability. Incorporating BSG into food products like pasta could leverage its nutritional advantages and appeal to consumers seeking healthier options.